Distinct Clinical Presentations of Vein of Galen Aneurysmal Malformation: A Case Series - Toktam Sheykhian; Behzad Mohammadpour Ahranjani; Saghi Elmi; Mohammadamin Parsaei (Clinical Case Reports)
ABSTRACT We present two cases of vein of Galen aneurysmal malformation, detected in early life, with differing outcomes. This suggests that early detection of this malformation in fetuses or neonates does not necessarily indicate a poor prognosis, highlighting the need for vigilant monitoring and timely intervention to optimize outcomes.